Borehole Resin Tapping in Chir Pine (Pinus roxburghii) - Rawat, G. S. (Indian Forester, 2000)
Studies were conducted on borehole resin tapping in chir pine (Pinus roxburghii) in order to standardize optimum depth and diameter of borehole including treatments to obtain maximum yield of resin. The maximum yield with minimum damage to the tree was obtained from the borehole of 15.24cm (6") depth and 2.54cm (1") diameter. The 10% ethepon concentration and etheJion with sulphuric acid were found most suitable for treatment of borehole to obtain maximum yield.